Examining the role of materialism, perceived stress and gender differences in compulsive buying behavior among young adults in Malaysia - Looi, Ke Xin; Tan, Kai Ni; Tee, Geok Hong (2022)
It was found that compulsive buying is a serious issue, especially while Malaysia was undergoing the Movement Control Order in 2020 to 2021, because there are more Malaysian young adults spending out of their affordable range and eventually, they go bankrupt. Hence, this study aims to examine the role of materialism, perceived stress and gender differences in compulsive buying behavior among young adults in Malaysia. A survey research design was applied. There were 209 respondents, consisting of 90 males (43.1%) and 119 females (56.9%) with the mean age of 22.02 years (SD = 1.602) recruited in the study through purposive and snowball sampling methods. An online questionnaire consisting of Material Values Scale, Perceived Stress Scale and Edwards Compulsive Buying Scale were distributed through online platforms, like Instagram and Microsoft Team. The result showed that materialism was a negative predictor of compulsive buying behavior, perceived stress was not a significant predictor of compulsive buying behavior and there was no significant gender difference in compulsive buying behavior among males’ and females’ young adults in Malaysia. This study has introduced a new perspective, whereby different types of materialists may have the different extent of engagement in compulsive buying behavior, besides contributing to the understanding of the current research topic in Malaysia context that is enriched with people from different cultures and materialism values. Meanwhile, the policymakers can develop financial programs to educate young adults in financial management based on the findings. This study also increases the awareness of marketers to practice marketing ethics.